PRODUKTIVITAS ALAT BERAT DUMP TRUCK PADA PEKERJAAN GALIAN DAN URUGAN TANAH DENGAN ALAT PEMUAT BACKHOE PC 78 PROYEK TAHAP 3 RUMAH SAKIT SITI KHODIJAH SIDOARJO - ERDYKA PUTRA RAMADHAN (Jurnal Vokasi Teknik Sipil, 2024)
In the use of heavy equipment, it is necessary to calculate productivity as a determination of the level of efficiency of the use of equipment and success in carrying out work, one of which is excavation and soil backfill. In the construction project of Phase 3 Building of Siti Khodijah Hospital Sidoarjo, it has an excavation volume of 2,572 m3 which is then excavated and moved to different locations for it requires the calculation of the productivity of heavy equipment dump trucks. With the use of the dump truck cycle time data collection method, then after the data is collected, calculations are carried out to determine the level of productivity of dump truck heavy equipment in excavation and soil backfill work using a PC 78 backhoe. Based on the results of calculations using the PC 78 backhoe loader, the productivity of the dump truck is 9,42 m3/hour. The results of the productivity of heavy equipment dump trucks in carrying out work activities are influenced by the optimal conditions of the equipment and the surrounding environment.